Analisis Capacity Requirement Planning pada Mesin Robotic Fiber Laser di PT. Kiyokuni Indonesia - Achmad Yusuf Ruswantoro; Dene Herwanto (Universitas Indraprasta PGRI Jakarta, 2021)
Inaccuracy in planning capacity requirements will cause the company to suffer losses. Such losses include disruption in the production process due to not taking into account the number of workers and machines needed to complete production activities. This study aims to determine the capacity that is owned and the production load received by the machines contained in PT. Kiyokui Indonesia, especially the Robotic Fiber Laser machine, uses the Capacity Requirement Planning method which functions to display the comparison between the load that is inaugurated at work centers through existing work orders and the capacity of each work center during a certain period of time. PT. Kiyokuni Indonesia is a company engaged in the production of printer parts that are produced from the stamping press and assisted by the Robotic Fiber Laser in performing assemblies. With very high customer demand demanding that the Robotic Fiber Laser machine has a workload of almost 24 hours, using the Capacity Requirement Planning method, it is known that in January and February the Robotic Fiber Laser machine has overloaded, where the capacity requirement is 58,673 minutes in January and in February. 38,891 minutes, then the available capacity in January and February was only 34,500 minutes which could not be fulfilled the capacity needs that it should have